International Monetary Fund Annual Report 2002 : Making the Global Economy Work for All. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2002)
The Annual Report to the Board of Governors reviews the IMF's activities and policies during any given year. There are five chapters: (1) Overview, (2) Developments in the Global Economy and Financial Markets, (3) Policies to Secure Sustained and Balanced Global Growth, (4) Reforming and Strengthening the IMF to Better Support Member Countries, and (5) Finances, Organization, and Accountability. The full financial statements for the year are published separately and are also available, along with appendixes and other supplementary materials.